2000
DOI: 10.1109/26.864167
|View full text |Cite
|
Sign up to set email alerts
|

Turbo decoding for partial response channels

Abstract: The partial response channel can be viewed as a rate-1 encoder in which the output alphabet differs from the input alphabet. In serially concatenated coding schemes, the partial response channel can serve as the inner encoder. Recent work on the application of turbo decoding techniques to partial response channels has focused on using a parallel concatenation of convolutional encoders as the outer code and the partial response channel as the inner code. This system requires three a posteriori probability (APP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…In this section the performance of all three decoding schemes is evaluated using computer simulations and compared to that of the benchmark scheme of [18], which does not employ the knowledge of the noise correlation. The recording densities of 2.25 and 2.86 are used.…”
Section: Performance Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section the performance of all three decoding schemes is evaluated using computer simulations and compared to that of the benchmark scheme of [18], which does not employ the knowledge of the noise correlation. The recording densities of 2.25 and 2.86 are used.…”
Section: Performance Resultsmentioning
confidence: 99%
“…We also investigated the convergence behavior of these four decoding schemes using different precoders and found that they obeyed similar trends. (L=scheme [18] iteration I1 10-5, coding gains in the range of 1-1.8 dB can be attained at a recording density of 2.25, whereas higher gains of 1.8-3.7 dB are achieved at the higher recording density of 2.86. This indicates that the three decoding schemes are capable of exploiting the knowledge of noise correlation very effectively, leading to performance improvement of the turbo decoding system in the magnetic recording channels in comparison to that of the benchmark scheme.…”
Section: B Performance Convergence Behaviormentioning
confidence: 99%
See 3 more Smart Citations